2022 Alzheimer's disease facts and figures (Alzheimer's & dementia, 2022)
This article describes the public health impact of Alzheimer's disease (AD), including incidence and prevalence, mortality and morbidity, use and costs of care, and the overall impact on family caregivers, the dementia workforce and society. The Special Report discusses consumers' and primary care physicians' perspectives on awareness, diagnosis and treatment of mild cognitive impairment (MCI), including MCI due to Alzheimer's disease. An estimated 6.5 million Americans age 65 and older are living with Alzheimer's dementia today. This number could grow to 13.8 million by 2060 barring the development of medical breakthroughs to prevent, slow or cure AD. Official death certificates recorded 121,499 deaths from AD in 2019, the latest year for which data are available. Alzheimer's disease was officially listed as the sixth‐leading cause of death in the United States in 2019 and the seventh‐leading cause of death in 2020 and 2021, when COVID‐19 entered the ranks of the top ten causes of death. Alzheimer's remains the fifth‐leading cause of death among Americans age 65 and older. Between 2000 and 2019, deaths from stroke, heart disease and HIV decreased, whereas reported deaths from AD increased more than 145%. More than 11 million family members and other unpaid caregivers provided an estimated 16 billion hours of care to people with Alzheimer's or other dementias in 2021. These figures reflect a decline in the number of caregivers compared with a decade earlier, as well as an increase in the amount of care provided by each remaining caregiver. Unpaid dementia caregiving was valued at $271.6 billion in 2021. Its costs, however, extend to family caregivers’ increased risk for emotional distress and negative mental and physical health outcomes — costs that have been aggravated by COVID‐19. Members of the dementia care workforce have also been affected by COVID‐19. As essential care workers, some have opted to change jobs to protect their own health and the health of their families. However, this occurs at a time when more members of the dementia care workforce are needed. Average per‐person Medicare payments for services to beneficiaries age 65 and older with AD or other dementias are almost three times as great as payments for beneficiaries without these conditions, and Medicaid payments are more than 22 times as great. Total payments in 2022 for health care, long‐term care and hospice services for people age 65 and older with dementia are estimated to be $321 billion. A recent survey commissioned by the Alzheimer's Association revealed several barriers to consumers’ understanding of MCI. The survey showed low awareness of MCI among Americans, a reluctance among Americans to see their doctor after noticing MCI symptoms, and persistent challenges for primary care physicians in diagnosing MCI. Survey results indicate the need to improve MCI awareness and diagnosis, especially in underserved communities, and to encourage greater participation in MCI‐related clinical trials.